The Effect of Doses of Various Types of Manure and NPK Mutiara on the Growth and Production of Pagoda Mustard (Brassica narinosa L.) - Marulam MT Simarmata (Jurnal Penelitian Pendidikan IPA, 2025)
This research was conducted in the Karangsari area, Gunung Maligas District, Simalungun Regency from December 2024 to February 2025. The purpose of this study was to determine the effect of doses of various types of manure and NPK Mutiara on the growth and production of pagoda mustard (Brassica narinosa L.). This study used a factorial Randomized Block Design (RAK) consisting of 2 factors, the first factor was the provision of various types of manure consisting of 4 treatment levels, namely K0 = no treatment, K1 = 2kg / chicken coop plot, K2 = 2kg / cow coop plot, K3 = 2 kg / goat coop plot. The second factor was the provision of NPK Mutiara fertilizer consisting of 3 treatment levels, namely: N1 = 20g / plot, N2 = 40g / plot, N3 = 60g / plot. Observed parameters: plant height (cm) at 14, 21 and 28 days after planting, number of leaves (strands) at 14, 21 and 28 days after planting DAP, gross weight per plant (g), net weight per plant (g), net weight per plot (kg). The results showed that the application of various types of manure, NPK Mutiara fertilizer, and a combination of both treatments on the growth and production of pagoda mustard greens showed a significant effect on plant height (cm) at 14, 21, and 28 DAP, number of leaves (blades) at 14, 21, and 28 DAP, gross weight per plant, gross weight per plot, net weight per plant, and net weight per plot. The best type of manure was chicken manure at a dose of 20 tons/ha, the best dose of NPK Mutiara fertilizer was at 600 kg/ha, and the best combination of both treatments was 20 tons/ha of chicken manure and 600 kg/ha of NPK Mutiara fertilizer.